A qualitative study of nutritional management needs of patients with ulcerative colitis from nurses' perspectives (护士视角下溃疡性结肠炎患者营养管理需求的质性研究) - LI Xumiao (李旭苗); LIANG Zhulin (梁琢琳); WEI Rongsai (魏荣赛); LIU Jingying (刘璟莹); ZHANG Nan (张楠); MA Hongwen (马宏文) (中西医结合护理)
Objective Based on nurses' perspectives, to explore the nutritional management needs of patients with ulcerative colitis (UC), and to provide a basis for optimizing clinical nursing practice. Methods Using purposive sampling method, 11 nurses in the gastroenterology department of a tertiary hospital in Tianjin were selected for semi-structured interviews (April-June 2024), and Colaizzi's phenomenological analysis was used to refine the themes. Results A total of 3 themes and 6 sub-themes were summarized: ①Health promotion: Nutritional knowledge popularization, improvement of service system; ②Patient perception: Information asymmetry, differences in psychological expectations; ③External support: Caregiver support, policy support. Conclusion The nutritional management needs of UC patients are multidimensional and dynamic, and caregivers need to combine individual patient differences, integrate multiple resources, and construct a personalized nutritional management model based on the characteristics of patients' different dietary nutrition in order to promote patients' recovery. (目的 基于护士视角, 探讨溃疡性结肠炎(UC)患者的营养管理需求, 为优化临床护理实践提供依据。方法 采用目的抽样法, 选取天津市某三级甲等医院消化科11名护士进行半结构式访谈(2024年4月—6月), 运用Colaizzi现象学分析法提炼主题。结果 共归纳出3个主题及6个亚主题: ①健康促进: 营养知识普及、服务体系完善; ②患者认知: 信息不对称、心理期望差异; ③外部支持: 照护者支持、政策支持。结论 UC患者营养管理需求具有多维性与动态性, 护理人员需结合患者个体差异, 整合多方资源, 根据患者不同饮食营养的特点, 构建个性化营养管理模式, 以促进患者的康复。)